2005
DOI: 10.1016/j.rmed.2004.04.018
|View full text |Cite
|
Sign up to set email alerts
|

High plasma concentrations of osteopontin in patients with interstitial pneumonia

Abstract: Osteopontin (OPN) produced by alveolar macrophages functions as a fibrogenic cytokine in the development of bleomycin (BLM)-induced murine pulmonary fibrosis, and OPN mRNA is expressed on lung tissues from patients with idiopathic pulmonary fibrosis (IPF). The present study investigates plasma OPN levels in human interstitial pneumonia (IP) and their relationships with disease severity by analyzing the correlation between plasma OPN concentrations and pulmonary functions. The concentrations of OPN in plasma we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 22 publications
4
51
0
Order By: Relevance
“…OPN is elevated in the BALF and plasma of IPF patients compared with healthy controls, but plasma levels are not significantly different from other ILDs (36,67). In a mix of ILD including IPF, plasma OPN levels correlated with oxygenation but not pulmonary function parameters (36). OPN gene expression is increased in the lung tissue of IPF patients with progressive disease compared with those with stable disease (11).…”
Section: Core Pathway 3: Fibroproliferation Fibrogenesis and Extracmentioning
confidence: 91%
See 1 more Smart Citation
“…OPN is elevated in the BALF and plasma of IPF patients compared with healthy controls, but plasma levels are not significantly different from other ILDs (36,67). In a mix of ILD including IPF, plasma OPN levels correlated with oxygenation but not pulmonary function parameters (36). OPN gene expression is increased in the lung tissue of IPF patients with progressive disease compared with those with stable disease (11).…”
Section: Core Pathway 3: Fibroproliferation Fibrogenesis and Extracmentioning
confidence: 91%
“…OPN induces upregulation of MMP7 in AECs and colocalizes with MMP7 in AECs of IPF lungs (67). OPN is elevated in the BALF and plasma of IPF patients compared with healthy controls, but plasma levels are not significantly different from other ILDs (36,67). In a mix of ILD including IPF, plasma OPN levels correlated with oxygenation but not pulmonary function parameters (36).…”
Section: Core Pathway 3: Fibroproliferation Fibrogenesis and Extracmentioning
confidence: 99%
“…Its role in promoting the migration, adhesion, and proliferation of fibroblasts has been demonstrated in a mouse model of bleomycininduced pulmonary fibrosis (29). A study in 2005 (30) found that levels of osteopontin in plasma were significantly higher in patients with ILDs than in those and SP-D had a worse 3-year survival rate.…”
Section: Osteopontinmentioning
confidence: 99%
“…39 A small study of 17 ILD patients and nine patients with sarcoidosis found significantly elevated levels of serum OPN in both conditions compared to controls; there was also a significant difference found between ILD and sarcoidosis patients, although IPF patients were statistically indistinguishable from other ILD conditions. 40 This study noted an inverse correlation with arterial partial pressure of oxygen (PaO 2 ) levels but not with pulmonary function test (PFT) values. There was no significant correlation between OPN and other biomarkers, including KL-6 and SP-A and SP-D. 40 Despite the above discoveries strongly supporting a role for OPN in the pathogenesis of IPF, the data are insufficient to support its use as a biomarker for IPF.…”
Section: Extracellular Signals Osteopontinmentioning
confidence: 77%
“…40 This study noted an inverse correlation with arterial partial pressure of oxygen (PaO 2 ) levels but not with pulmonary function test (PFT) values. There was no significant correlation between OPN and other biomarkers, including KL-6 and SP-A and SP-D. 40 Despite the above discoveries strongly supporting a role for OPN in the pathogenesis of IPF, the data are insufficient to support its use as a biomarker for IPF.…”
Section: Extracellular Signals Osteopontinmentioning
confidence: 77%